Muscle contraction velocity: a suitable approach to analyze the functional adaptations in elite soccer players - Loturco, I.; Pereira, L. A.; Kobal, R.; Kitamura, K.; Ramirez-Campillo, R.; Zanetti, V.; Cal Abad, C. C.; Nakamura, F. Y. (Journal of Sports Science & Medicine, 2016)
Tensiomyography (TMG) has been used as a simple and non-invasive tool to assess the mechanical properties of skeletal muscles. The TMG-derived velocity of contraction (Vc), which can be calculated from the ratio between maximal radial displacement and the sum of contraction time and delay time, has been proposed for evaluating athletes. However, its sensitivity to training effects and possible relation with changes in soccer players` neuromuscular performance have not yet been addressed. To test this possibility, twenty-two male Brazilian elite soccer players were assessed using TMG-derived Vc, unloaded squat jump, countermovement jump and drop jump at 45 cm, loaded jump squat and linear (20 m) and change of direction (COD) sprint tests, prior to and after an 8-week period, between two consecutive official tournaments, during which the concurrency between endurance and strength-power training commonly impairs neuromuscular capacities. Magnitude-based inference was used to detect meaningful training effects. From pre- to post-tests, it was observed likely to almost certainly improvements in all modes of jumping tests. In addition, we could verify decrements in the 20-m and COD sprint performances, which were rated as very likely and almost certainly, respectively. Finally, both rectus femoris and biceps femoris muscles presented a likely reduction in Vc. Therefore, chronic decreases in sprinting speed are possibly accompanied by a reduced TMG-derived Vc. From a practical standpoint, the TMG-derived Vc can be used to monitor negative specific-soccer training effects related to potential impairments in maximum speed.